The Anti-Secular Regulation of Religious Difference in Egypt - Azmi, Meriam Wagdy (AUC Knowledge Fountain, 2021)
Egyptian religious freedom activists and researchers have for decades called for more secularism to remedy the violations facing religious minorities. Those religious minorities have been subject to attacks for practicing religious rituals and suffered from lack of recognition by the government. As those activists advocated secularism, some academics critiqued it and deemed it the instigator of the very problems it claims to uproot. Saba Mahmood famously argued that secularism is a primary producer of religious tension in Egypt. In this thesis, I argue that it is not the mere regulation of religious difference as a feature of secularism that is the problem, but the manner in which Egypt does the regulation, in which it empowers religious institutions and espouses Islam as its quintessential identity and Shari'a the basis of its public order. I also conclude that despite secularism’s inherent problems, it continues to hold promise for some change for Egypt’s minorities. I reach that conclusion by testing Mahmood’s argument against key legal events post-2013: The 2014 Constitution, the Church Construction Law, and the yet to be issued Personal Status Law for non-Muslims.